The Great Dimming of Betelgeuse from the VLT/VLTI. Issue Volume 16:Issue S366(2020) (November 2020) - Montargès, M.; Cannon, E.; Lagadec, E.; de Koter, A.; Kervella, P.; Sanchez-Bermudez, J.; Paladini, C.; Cantalloube, F.; Decin, L.; Scicluna, P.; Kravchenko, K.; Dupree, A. K.; et al.
Abstract: From November 2019 to April 2020, the prototypical red supergiant Betelgeuse experienced an unexpected and historic dimming. This event was observed worldwide by astrophysicists, and also by the general public with the naked eye. We present here the results of our observing campaign with ESO's VLT and VLTI in the visible and infrared domains. The observations with VLT/SPHERE-ZIMPOL, VLT/SPHERE-IRDIS, VLTI/GRAVITY and VLTI/MATISSE provide spatially resolved diagnostics of this event. Using PHOENIX atmosphere models and RADMC3D dust radiative transfer simulations, we built a consistent model reproducing the images and the photometry.